Absolute polarization determinations of 33 pulsars using the Green Bank Telescope. Issue 4 (17th September 2015) - Force, Megan M.; Demorest, Paul; Rankin, Joanna M.
Abstract: Absolute polarimetry observations of 33 pulsars were carried out with the Green Bank Telescope in the 1100–1900 MHz band using the Green Bank Ultimate Pulsar Processing Instrument. This group was selected to help complete a larger sample for which accurate proper-motion measurements were available. A combination of profile analysis using the core/double cone model and polarization-angle fitting methods were applied to estimate the 'fiducial' longitude of the magnetic axis for each star and refer the linear polarization angle at that point to infinite frequency. As had been found previously, a number of the pulsars are found to have fiducial polarization directions that fall either along or at right angles to their proper-motion directions, whereas upwards of a third of the stars studied show alignments that are neither parallel nor orthogonal.